1980
DOI: 10.1128/jb.144.1.114-123.1980
|View full text |Cite
|
Sign up to set email alerts
|

Are growth rates of Escherichia coli in batch cultures limited by respiration?

Abstract: Batch cultures of Escherichia coli were grown in miniimal media supplemented with various carbon sources which supported growth at specific growth rates from 0.2 to 1.3/h. The respiration rates of the cultures were measured continuously. With few exceptions, the specific rate of oxygen consumption was about 20 mmol of O2/h per g (dry weight), suggesting that the respiratory capacity was limited at this value. The adenosine triphosphate (ATP) required for the production of cell material from the different carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
108
0
3

Year Published

1988
1988
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(130 citation statements)
references
References 32 publications
19
108
0
3
Order By: Relevance
“…metabolic over-flow products and other metabolites, excreted proteins, cell wall components and other lyric products [37,38], For example, from the Grampositive bacilli it is known that large cell wall particles are sloughed off into the medium dug to the specific mechanism of growth of the peptidoglycan layer [39,401. F,. coli is known to excrete significant amounts of acetate and probably other compounds during exponential growth with glucose [41]. Our own results with K. pneumoniae confirm this observation with approximately 5-10% of the metabolized carbon being excreted in the form of acetate (Figs.…”
Section: Product Formation and Reutilizationsupporting
confidence: 79%
See 1 more Smart Citation
“…metabolic over-flow products and other metabolites, excreted proteins, cell wall components and other lyric products [37,38], For example, from the Grampositive bacilli it is known that large cell wall particles are sloughed off into the medium dug to the specific mechanism of growth of the peptidoglycan layer [39,401. F,. coli is known to excrete significant amounts of acetate and probably other compounds during exponential growth with glucose [41]. Our own results with K. pneumoniae confirm this observation with approximately 5-10% of the metabolized carbon being excreted in the form of acetate (Figs.…”
Section: Product Formation and Reutilizationsupporting
confidence: 79%
“…Biomass concentration in the stationary phase usually remains constant for several hours. This has been clearly demonstrated in a number of instances including E. coil [41], B. natriegens [45,531 and K. pneumoniae (Fig. 8).…”
Section: Carbon and Energy Exhaustionmentioning
confidence: 77%
“…The absence of a relationship between biomass and phytase synthesis in the present study could be due to an increased accumulation of fermentation by-products, such as lactic acid, succinic acid and acetic acid, in the medium which may depress phytase synthesis. Anderson and Meyenburg (1980) found that glucose feeding led to a bacterial ÔCrabtree effectÕ under aerobic conditions, resulting in the formation of acetate and other metabolic by-products. Meyer et al (1984) pointed out that when complex (instead of defined) media were supplemented with glucose as an additional carbon source, a faster reduction in growth rate Means with different superscripts in the same row are significantly different (P < 0AE05).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the precise supplements required for a specific biological system or strain, the general influences of some medium components on recombinant gene expression have been described and studied. Among them, glucose-mediated inhibition of cell growth (Andersen and von Meyenburg, 1980) and product yield (Rinas et al, 1989;Vila and Villaverde, 1993) is of relevant interest because this sugar is often employed as a carbon source in defined media or even as a supplement in complex media. In general, all of the essential substrates for bacterial growth are toxic to the cells beyond critical thresholds, which are specific for each particular strain, medium, and growth conditions.…”
Section: Introductionmentioning
confidence: 99%